Correlations among satisfaction parameters after orthodontic treatment - Eftychia LAMPRAKI; Fanouria PAPAIOANNOU; Ioulia-Maria MYLONOPOULOU; Nikolaos PANDIS; Iosif SIFAKAKIS (Dental Press Editora, 2024)
ABSTRACT Objective: This study assessed patient's satisfaction after orthodontic treatment in the postgraduate orthodontic clinic of the Dental School at the University of Athens (Athens, Greece), and investigated possible correlations between satisfaction after orthodontic treatment and life satisfaction, alongside the influence of age, gender, severity of initial orthodontic malocclusion and duration of retention period. Material and Methods: Patients aged 12 years and above, who had recently completed comprehensive orthodontic treatment, participated completing two questionnaires: a 37-item questionnaire, validated for assessing orthodontic treatment satisfaction; and the 5-item Satisfaction with Life Scale, a valid and reliable measure of life satisfaction. Scores from each questionnaire were summed for each patient. Demographic details, Index of Orthodontic Treatment Need (IOTN) and the duration of the retention period up to questionnaire completion were collected. Multiple regression analysis assessed the relationship between the questionnaires and the evaluated variables. Results: A total of 150 patients answered the questionnaires, being 82 women (55%) and 68 men (45%). The mean age of patients was 18.87 ± 5.97 years (range: 12-47). Most patients expressed satisfaction with treatment outcomes (grades 5 and 6). Satisfaction with orthodontic treatment showed a significant correlation with life satisfaction (p=0.002), but not with gender, age, dental/esthetic components of IOTN, or the duration of the retention period. Conclusion: Satisfaction after orthodontic treatment exhibited a significant correlation with life satisfaction, but it was not affected by gender, age, dental/esthetic components of IOTN, or the duration of the retention period.